Mulberry Paper‐Based Supercapacitor Exhibiting High Mechanical and Chemical Toughness for Large‐Scale Energy Storage Applications. Issue 21 (23rd April 2018) - Yun, Tae Gwang; Kim, Donghyuk; Kim, Sang‐Min; Kim, Il‐Doo; Hyun, Seungmin; Han, Seung Min
Abstract: In response to the demand for flexible and sustainable energy storage devices that exhibit high electrochemical performance, a supercapacitor system is fabricated using mulberry tree‐derived paper as a substrate and Poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) and carbon black as the active material. The mulberry paper‐based supercapacitor system demonstrates high energy density of 29.8–39.8 Wh kg −1 and power density of 2.8–13.9 kW kg −1 with 90.7% retention of its initial capacity over 15 000 charge–discharge cycles. In addition, the mulberry tree fibers are known to have superior mechanical strength and toughness and the mulberry paper‐based supercapacitor; as a result, exhibit high mechanical and chemical toughness; 99% of its initial capacity is retained after 100 repeated applications of bending strains, and twisting. 94% capacity retention is observed even after exposure to HCl and H2 SO4 acid solutions. The fabrication methodology of the mulberry‐based supercapacitor is highly scalable and could be stacked to increase the energy storage capacity, where operation of light‐emitting diode lights with a drive voltage of 12 V integrated in a wearable device is demonstrated. Abstract : A supercapacitor system is fabricated using mulberry tree‐derived paper as a substrate and PEDOT:PSS and carbon black as the active material . The mulberry tree fibers are known to have superior mechanical strength and toughness and therefore, the mulberry paper‐based supercapacitor exhibits high mechanical and chemical toughness as well as high capacitance for potential large‐scale and wearable energy storage application.